(untitled) (Research, Society and Development, 2022)
Objective: to validate the content of a standard operating procedure with interventions by nurses to carry out the virtual family visit to the patient with coronavirus hospitalized in a Coronary Intensive Care Unit. Method: Methodological study with a quantitative approach, carried out from January to August 2021, with content validation of a standard operating procedure built from an integrative review. Validation by experts was carried out through an electronic form, regarding agreement, coherence, objectivity, relevance and content. For validation, the Content Validity Coefficient (>0.85) and the Content Validity Index (> 0.85) were used in one round. Results: the standard operating procedure consisting of three domains and 43 items was validated by 15 judges with a content validity index of 0.98, considered excellent and with high reliability with a value of 0.89. Conclusion: Based on the results, it is recommended that the validated technological instrument be used in the practice of nurses during the virtual family visit.